Letter - Schevenels, Walther, b. 1894
013-0110-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe IFTU Sch/H TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 48-88 EXECUTIVE COMMITTEE : President : W. M. Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; M Meister, Switzerland; Corn. Mertens, Belgium General Secretary : W Schevenels Letter Sec ref div No. 293 AFFILIATED COUNTRIES ARGENTINE BELGIUM CANADA CHINA CZECHOSLOVAKIA DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN HOLLAND HUNGARY INDIA LUXEMBURG MEXICO NEW ZEALAND NORWAY PALESTINE POLAND RUMANIA SPAIN SWEDEN SWITZERLAND UNITED STATES YUGOSLAVIA PRIVATE 24th February 1940 Mr. Walter M. Citrine, London. Dear Comrade Citrine, With reference to our last conversation, I should like to remind you of my request concerning the former General Secretary of the UGT, Comrade Jose Rodriguez Vega. I have been informed that Comrade Vega will be coming before a court martial in Madrid in a day or two, and it is feared that a death sentence will be pronounced. Apart from Comrade Vega's political attitude in the earlier days of the civil war in Spain, I must say that, from 1937 onwards, this comrade took a very courageous stand and defended unreservedly the IFTU and its activities in the Spanish affair. If you find it in any way possible to use your personal influence with the British authorities with a view at least to saving Comrade Vega's life, our Spanish friends, many other comrades and I myself will be extremely grateful. Thanking you in advance, Yours sincerely, W. Schevenels, General Secretary: 292/946/13/110